2012
DOI: 10.1177/1474022212467605
|View full text |Cite
|
Sign up to set email alerts
|

Making judgements about students making work: Lecturers’ assessment practices in art and design

Abstract: This document is the author deposited version. You are advised to consult the publisher's version if you wish to cite from it. Published versionORR, Susan and BLOXHAM, Sue (2013). Making judgements about students making work : lecturers' assessment practices in art and design. Arts and Humanities in Higher Education, 12 (2-3), 234-253. Copyright and re-use policy AbstractThis research study explores the assessment practices in two higher education art and design departments. The key aim of this research was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
1
8
0
2
Order By: Relevance
“…The Architecture case provides some support for that position in that the portfolio represented both a final summative product and formative processes of iteration, feedback and self-evaluation underpinning its development. This resonates with the position of Orr and Bloxham (2012) who assert that in Art and Design students' development work and final work are assessed in their totality, challenging the notion of the separation of formative and summative assessment. This scope for interweaving of teaching, learning and assessment is something teachers in other contexts or disciplines might strive to emulate.…”
Section: Discussionsupporting
confidence: 59%
“…The Architecture case provides some support for that position in that the portfolio represented both a final summative product and formative processes of iteration, feedback and self-evaluation underpinning its development. This resonates with the position of Orr and Bloxham (2012) who assert that in Art and Design students' development work and final work are assessed in their totality, challenging the notion of the separation of formative and summative assessment. This scope for interweaving of teaching, learning and assessment is something teachers in other contexts or disciplines might strive to emulate.…”
Section: Discussionsupporting
confidence: 59%
“…Gaining consensus on judgement decisions can mask the level of academic engagement that has occurred in the moderation discussion. Consensus can be reached by agreeing on marks, yet with little reference to the evidence used to justify decisions, or with unjustified reference to evidence not listed in the criteria (Orr and Bloxham 2013). While such consensus may satisfy the need for accountability and reassure markers in responding to students' queries, it hardly assures the fidelity of the final grade.…”
Section: Moderation Discussion (Consensus/social Moderation)mentioning
confidence: 99%
“…Students' awareness of the power relations between themselves and their tutors helps to explain why some of them might enjoy so-called 'active' learning less than lectures, and also why the experience of receiving feedback is perceived by them as demotivating and unfair. Research has shown that tutors often make judgements about students, (not just their work), when marking and giving feedback (Orr 2010;Orr and Bloxham 2013). Research also shows that, far from being supported and enabled, students often feel disempowered by feedback from tutors, which they see as reflecting the values of the tutor (Blair 2007;Winstone et al 2017), rather than a recognition of the student's own values and ambitions.…”
Section: Student Engagementmentioning
confidence: 99%